Study of Antiobesity Effect through Inhibition of Pancreatic Lipase Activity of Diospyros kaki Fruit and Citrus unshiu Peel. (27th July 2016) - Kim, Gyo-Nam; Shin, Mi-Rae; Shin, Sung Ho; Lee, Ah Reum; Lee, Joo Young; Seo, Bu-Il; Kim, Min Yeong; Kim, Tae Hoon; Noh, Jeong Sook; Rhee, Man Hee; Roh, Seong-Soo
Abstract : Pancreatic lipase is the enzyme responsible for digestion and absorption of triglycerides, being its inhibition one of the widest studied methods used to determine the potential activity of natural products to inhibit dietary fat absorption. Decrease of energy intake from dietary fat through inhibition of this enzyme may be an excellent strategy to prevent and treat obesity. The inhibitory activity on pancreatic lipase enzyme of Diospyros kaki fruit and Citrus unshiu peel mixture extract (PCM) was evaluated in vitro and its antiobesity effects were studied based on the serum lipid parameters analysis from high-fat diet- (HFD-) fed mice in vivo . PCM was orally administered at a dose of 50 and 200 mg/kg body weight for 6 weeks. In addition, the activity of pancreatic lipase was assessed using orlistat (positive control). PCM exhibited inhibitory effect on lipase activity with IC50 value of 507.01  μ g/mL. Moreover, serum triacylglycerol, total cholesterol levels, and visceral fat weight were significantly reduced compared to HFD control mice in PCM 200 mg/kg-treated mice (p < 0.05 ). These results suggest that PCM administration may be a novel potential antiobesity agent for reduction of fat absorption via inhibition of pancreatic lipase.